Marketing Plan for a Footwear Company – Part 2 (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of this paper was to conduct a marketing plan of a Footwear Company in Durban, South Africa. The marketing plan strategies for growth was determined using the Boston Consulting Group (BCG) matrix. The marketing mix was discussed using the 4Ps. Communications and marketing tactics was described using the integrated marketing communications process and promotional tools. The implementation and evaluation were set out against the objectives, timescales, key performance indicators and budget. Successful implementation and evaluation of the plan will ensure the Footwear Company sustains and improves its success and meets the expectations of its stakeholders.